Diagnostic approach to limbal stem cell deficiency - Lent-Schochet, Daniella; Akbar, Mizna; Hou, Joshua H.; Farooq, Asim V. (Frontiers in Ophthalmology, 2025)
Limbal stem cell deficiency (LSCD) is an important cause of visual and ocular morbidity. Effective diagnosis and management require a thoughtful and comprehensive evaluation of the ocular surface. This review describes the pathogenesis, diagnosis, and grading of LSCD, as well as characteristic findings via slit lamp examination, in-vivo confocal microscopy, anterior segment optical coherence tomography (AS-OCT), impression cytology, and OCT angiography.